PERAN GURU DALAM PERKEMBANGAN MORAL DAN KEPRIBADIAN SISWA SEKOLAH DASAR - Salmiyanti, Salmiyanti; S, Neviyarni; Desyandri, Desyandri (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
The teacher as an element in the teaching and learning process has multiple roles, not limited only as a teacher who only transfers knowledge but also as a mentor who encourages potential, develops alternatives and mobilizes students in learning. The aim of this research is to describe the teacher's role in the moral and personality development of elementary school students. This research uses the method of literature research research or literature study by examining various journals that have links or relationships with the teacher's role in the moral and personality development of elementary school students. The results of the study show that teachers have several roles in dealing with students, namely; corrector, inspirer, informator, organizer, motivator, initiator, facilitator, mentor, demonstrator, class manager, mediator, supervisor and evaluator. Moral values ​​and personality are a measure of the rightness or wrongness of an action, behavior and attitude of a person towards others and towards their environment.